A sociological understanding of contemporary child marriage in Mabvuku, Harare, Zimbabwe - Madzivire, Shamso Christine (Rhodes University, Faculty of Humanities, Department of Sociology, 2020)
Child marriage is a phenomenon that has been increasingly recognised as a global problem since the late nineteenth century. Since then, scholars across many disciplines along with various agencies such as government bodies and non-governmental organisations have tirelessly engaged in research exploring the causes and consequences of this practice and in developing prevention and mitigation strategies. These research efforts have been concentrated in some parts of the world and not others, with the findings in many cases being generalised problematically across different geographical areas. This thesis stands as a response to the dearth of academic research on child marriage in present-day Zimbabwe and simultaneously highlights the significance of studying the specificities of child marriage under particular historical and spatial conditions. The main objective of this thesis is to explore and understand child marriage as a part of modernday marriage practices in Zimbabwe, through a case study of child marriage in Mabvuku in Harare. In addressing this objective, it is hoped that new ways of thinking around this phenomenon will become evident. In addressing this main objective, the thesis considers the experiences of child brides, the drivers and consequences of child and post-child marriage experiences. It does this seeking to understand child marriage with reference to the types of marital unions which exist amongst Shona people in pre-colonial times and in post-colonial Zimbabwe. The thesis adopts a qualitative research methodology which involved in-depth semistructured interviews with 25 women in Mabvuku who were married before the age of 18, along with focus group discussions with community workers and interviews with pertinent government and non-government representatives. Due to certain challenges with current theorising about child marriage, there is an attempt to build theory by drawing upon in particular the Zimbabwean notion and practice of hunhu. A key conclusion is that child marriage in present-day Zimbabwe is in part a result of family transitions which arose during the time of colonialism and continue to this day.
Keywords: Child marriage -- Zimbabwe -- Mabvuku; Child marriage -- Zimbabwe -- Case studies; Shona (African people) -- Social life and customs; Marriage customs and rites -- Zimbabwe; Shona (African people) -- Marriage customs and rites; Marriage -- Zimbabwe